Effect of thermal processing on total polyphenol content in the grain of cowpea cultivars - Rodrigo Barbosa Monteiro Cavalcante; Marcos Antônio da Mota Araújo; Maurisrael de Moura Rocha; Kaesel Jackson Damasceno e Silva; Regilda Saraiva dos Reis Moreira-Araújo (Revista Ciência Agronômica)
ABSTRACT Cowpea grain is noteworthy due to its functional properties, which are probably a result of the synergistic action of its nutrients and bioactive compounds. Since these compounds undergo the effects of thermal processing, the aim of the present study was to verify the influence of cooking on the total polyphenol content of the grain of cowpea cultivars. Samples were obtained from the experimental area of Embrapa Meio-Norte, located at 5°5' S and 42°48' W, at an altitude of 72 metres. Meal (0.5 mesh) resulting from the raw grain being ground in a cyclone rotor mill (Tecnal model TE-651/2-T), and cooked beans (with no maceration, at a bean to water ratio of 1:5 (w/v), cooked in a domestic pressure cooker (2 L) for 780 seconds) were stored in airtight containers under refrigeration (8 °C) for analysis, which was carried out in triplicate. Total phenolic content was determined by spectrophotometry (λ = 765 nm), using Folin-Ciocalteau reagent. The total phenolic content, mg GAE (gallic acid equivalent)/100g, in the raw grain of the BRS Marataoã, BR 17-Gurguéia, BRS Itaim, BRS Cauamé and BRS Guariba cultivars was 295.23, 255.67, 132.32, 98.14 and 89.43 respectively. After cooking, the content was 405.87, 255.4, 161.71, 127.79 and 111.92 respectively, considering both grain and broth. This rise may have been the result of increased solubilisation and extraction of the compounds, due to the softening or rupture of the plant cells. It was concluded that, considering both grain and broth, the total phenolic content increased after cooking; the BRS Marataoã and BR 17-Gurguéia cultivars showed the highest levels.